2020
DOI: 10.3390/pathogens9090701
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Non-H2S-Producing Monophasic Salmonella Typhimurium ST3478 Strains from Chicken Meat at Processing Stage Are Adapted to Diverse Stresses

Abstract: Poultry products are still an important cause of Salmonella infections worldwide, with an increasingly reported expansion of less-frequent serotypes or atypical strains that are frequently multidrug-resistant. Nevertheless, the ability of Salmonella to survive antimicrobials promoted in the context of antibiotic reducing/replacing and farming rethinking (e.g., organic acids and copper in feed/biocides) has been scarcely explored. We investigated Salmonella occurrence (conventional and molecular assays) among c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Of note is also the presence of gad (glutamate decarboxylase acid response system) in all but one of the E. coli genomes, associated with acid tolerance and directly related to the successful colonization of the mammalian host (De Biase and Pennacchietti, 2012). In fact, a stress factor like acid pH can occur at poultry farm level (e.g., organic acids as a feed additive, the gastrointestinal tract of the animals) or in the processing plant, mostly due to the widespread use of acidic surface/equipment disinfectants in the food industry (e.g., peracetic acid), as previously described (Mourão et al ., 2020a). However, further studies to explore combinations of genetic markers that might be involved in enhanced poultry/human colonization and persistence (e.g., for extended periods at farm level or in the gut) are needed to hamper these bacteria (including the emerging E. coli hybrid‐pathogenic strains) from spreading from the food chain to humans.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is also the presence of gad (glutamate decarboxylase acid response system) in all but one of the E. coli genomes, associated with acid tolerance and directly related to the successful colonization of the mammalian host (De Biase and Pennacchietti, 2012). In fact, a stress factor like acid pH can occur at poultry farm level (e.g., organic acids as a feed additive, the gastrointestinal tract of the animals) or in the processing plant, mostly due to the widespread use of acidic surface/equipment disinfectants in the food industry (e.g., peracetic acid), as previously described (Mourão et al ., 2020a). However, further studies to explore combinations of genetic markers that might be involved in enhanced poultry/human colonization and persistence (e.g., for extended periods at farm level or in the gut) are needed to hamper these bacteria (including the emerging E. coli hybrid‐pathogenic strains) from spreading from the food chain to humans.…”
Section: Resultsmentioning
confidence: 99%
“…Several different clones of different MDR Salmonella serovars isolated by placing polystyrene mats beneath a poultry processing line were able to persist on surfaces for several weeks and showed substantial biofilm formation (Dantas et al., 2020), which supports longitudinal studies that have identified resident MDR Salmonella in the poultry slaughterhouse environment (Shang et al., 2019), as well as ineffective cleaning and disinfection of poultry transport crates (Moazzami et al., 2020). Persistent AMR and heavy metal resistant bacteria that have enhanced stress response characteristics and biochemical changes that compromise detection may be selected after exposure to biocides (Mourão et al., 2020; Rhouma et al., 2020). L. monocytogenes strains isolated from the poultry processing environment can also form biofilm, with benzalkonium chloride‐based cleaning programmes showing limited efficacy and exacerbating biofilm formation and AMR expression (Cadena et al., 2019; Rodríguez‐Campos et al., 2019; Puangseree et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Serovar‐to‐serovar differences can create challenges in eliminating Salmonella during poultry processing, and it is possible that processing interventions are selecting for phenotypic differences. Many recent studies have suggested that some Salmonella serovars can survive processing interventions and some can persist in the environment (Eastwood et al, 2021; Mourão et al, 2020; Obe et al, 2020). For example, the susceptibility of several Salmonella isolates in different serovars were evaluated and Salmonella serovars Enteritidis and Typhimurium showed the most resistance to benzalkonium chloride, a quaternary ammonium compound (Long et al, 2016).…”
Section: Introductionmentioning
confidence: 99%